Deployment of Improved ID3 algorithm with Havrda and Charvat entropy for Employees performance evaluation - Kirandeep, Kirandeep; Madan, Neena (International Journal of Computer Sciences and Engineering, 2025)
In industrial sector, employee performance evaluation has paramount importance which will be used for predicting the performance of an employee or a number of employees by considering various aspects like employee’s task type, job skills, working quality, interpersonal relationship, creativity, adherence to policy, productivity, attendance, performance etc. Data mining consists of different techniques used to complete our objectives. Using this particular research, the industry superiors will have the ability to predict the performance of employees in an organization. The decision tree method is used on the database of an employee or a number of employees in order to analyze an employee data to make a prediction. Data mining is a tool which allows us to manage the data in a superior way